Endocrine control of sexual behavior in sneaker males of the peacock blenny Salaria pavo: Effects of castration, aromatase inhibition, testosterone and estradiol - Gonçalves, David (2012)
The effects of castration and sex steroid manipulations on the expression of sexual behavior were investigated in a small fish, the peacock blenny, Salaria pavo. In this species, large males defend nests and attract females while small “sneaker” males reproduce by imitating the female morphology and courtship behavior in order to approach nests during spawning events and parasitically fertilize eggs. Sneakers switch into nest holders in their second breeding season, thus displaying both male and female-like sexual behavior during their lifetime. We tested the effects of castration and of an aromatase inhibitor (Fadrozole, F), testosterone (T) or 17β-estradiol (E2) implants on the expression of male and female-like behavior in sneakers. Sneakers were either sham-operated, castrated or castrated and implanted with vehicle, F, T+F or E2+F. Seven days after the treatment, sneakers were placed in a tank with a nesting male, two ripe females and an available nest. Castrated fish had lower levels of circulating T and increased the time spent displaying female typical nuptial coloration. T implants had the opposite effect, inhibiting the expression of femalelike behavior and coloration. E2 implants had no significant effect on the display of sexual behavior but the frequency of aggressive displays decreased. The results agree with previous findings in sneakers of S. pavo that demonstrated an inhibition of female-like behavior by 11- ketotestosterone (11-KT). The reported increase in T and 11-KT production when sneakers change into nest holders may thus contribute to behaviorally defeminize sneakers. Contrarily, both T and E2 failed to promote male-like behavior, suggesting that behavioral masculization during tactic switching depends on other neuroendocrine mechanisms or that the time length of the experiment was insufficient to induce male-like behavioral changes in sneakers.